KEY ELEMENTS OF A DIGITAL URBANIZATION STRATEGY FOR TURKEY: INSIGHTS FROM PSYCHOMETRIC TESTING - Zeynep Demirci (International Scientific and Current Research Conferences, 2025)
Background: Urbanization in Turkey has rapidly accelerated in recent decades, necessitating the adoption of digital technologies to foster sustainable, efficient, and inclusive cities. The concept of digital urbanization, which integrates Information and Communication Technologies (ICT), smart city frameworks, and digital governance, is vital for addressing contemporary urban challenges. However, the successful implementation of digital urbanization strategies requires understanding the attitudes and perceptions of citizens, which can be measured through psychometric testing. Objective: This study aims to identify the key elements for developing a digital urbanization strategy for Turkey by utilizing psychometric testing to measure the public's attitudes, trust, concerns, and willingness to engage with digital urbanization initiatives. Methods: A quantitative psychometric approach was used to survey 1,500 participants from various regions of Turkey, ensuring a diverse demographic sample that included urban, suburban, and rural populations. The survey consisted of 40 questions divided into four sections: awareness of digital urbanization, trust in digital infrastructure, perceived benefits and concerns, and willingness to participate in digital urbanization. Data were analyzed using factor analysis to identify underlying factors and regression analysis to determine significant predictors of support for digital urbanization. Results: The study found that while 60% of respondents were familiar with the concept of digital urbanization, there was a notable lack of detailed knowledge regarding specific technologies. Trust in digital infrastructure was relatively low, with 45% of respondents expressing concerns about security and privacy. Despite these concerns, a majority (72%) recognized the potential benefits of digital urbanization, such as improved public services and traffic management. However, 52% were worried about job displacement due to automation, and 47% expressed concerns about the exclusion of marginalized groups. Approximately 65% of participants were open to engaging in digital governance and providing feedback on urban development projects. Discussion: The findings highlight several critical factors for developing a successful digital urbanization strategy in Turkey. These include increasing digital literacy, ensuring data security and privacy, bridging the digital divide between urban and rural areas, and fostering greater citizen participation in digital governance. Public trust can be enhanced by implementing transparent policies on data use and ensuring inclusivity in the provision of digital infrastructure. Conclusion: Digital urbanization in Turkey offers significant opportunities for improving urban living, but its success will depend on addressing public concerns related to privacy, security, and inclusivity. The results from psychometric testing provide valuable insights that can guide the development of a comprehensive, citizen-centered digital urbanization strategy, fostering sustainable and inclusive cities for the future.